Thoracic endovascular aortic repair for type B aortic dissection with aberrant right subclavian artery: a single-center retrospective study - Zeng, Yanzhang; Yuan, Ping; He, Qiang (Frontiers in Cardiovascular Medicine, 2023)
Objective To evaluate the outcomes of thoracic endovascular aortic repair (TEVAR) for type B aortic dissection (TBAD) with aberrant right subclavian artery (ARSA). Methods A retrospective analysis was conducted on patients with TBAD and ARSA who underwent TEVAR between the period of January 2017 and December 2022. Patient demographics, computed tomography angiography (CTA) measurements, surgical procedures, and postoperative outcomes were reviewed. Results A total of 9 patients (6 males and 3 females) were included in the study. 4 ARSA were reconstructed, 3 by periscope technique and 1 by in vitro fenestration technique. 3 left subclavian arteries (LSA) were reconstructed, 1 by the chimney technique and 2 by the single-branched stent technique. 2 patients underwent reconstruction of both ARSA and LSA. The overall technical success rate was 100%, with no occurrences of stroke, paraplegia, or mortality within 30 days. 1 patient experienced immediate type Ia endoleak, which resolved after 3 months. 1 patient developed weakness in the right upper limb, while 1 patient presented mild subclavian steal syndrome (SSS); both cases showed recovery during follow-up. The average follow-up duration was 35.6 ± 11.1 months, during which no reinterventions, deaths, or strokes were observed. Conclusion Our limited experience involving 9 patients demonstrates that early and mid-term outcomes of TEVAR for the treatment of TBAD with ARSA are satisfactory.